Sistem Manajemen K3 Pembuatan Kapal Fiberglass Dengan Metode Job Safety Analisis pada Galangan kapal Fiberglass Di Benowo, Surabaya – Jawa Timur - Muhammad Angga Alfarizy; Umi Chotijah; Yulia Ayu Nastiti (CV. ALIM'SPUBLISHING, 2025)
Dangerous chemicals are always used when building new fiberglass boats which can have a negative impact on human safety and health. Fiberglass boat building also involves the use of potentially dangerous work equipment. Because the risk aspects that cause work accidents have not been identified, work accidents often occur at this fiberglass boat manufacturing company, with an average of 15 work accidents per year. With this background, the author identifies the risk of work accidents, determines the risk value and identifies alternative solutions. Identification of work accident risks is carried out using the Job Safety Analysis (JSA) method and calculating risk values ​​according to ISO 45001:2018. After identifying the risk of work accidents in the process of building new fiberglass ships at this shipbuilding company, 25 potential risks were found. The risk score calculation according to ISO 45001:2018 classifies 11 potential risks into medium risk and high risk levels. The potential risk of work accidents when cutting wood to make molds is the occurrence of scratches and limbs being cut and lacerations and even permanent physical disability due to the grinding blade coming loose while the grinding process is in progress. This shows that there is a potential risk that has reached the High Risk level and must be followed up as quickly as possible.